Geomicrobiological Features of Ferruginous Sediments from Lake Towuti, Indonesia - Vuillemin, Aurèle; Friese, André; Alawi, Mashal; Henny, Cynthia; Nomosatryo, Sulung; Wagner, Dirk; Crowe, Sean A.; Kallmeyer, Jens (Frontiers in Microbiology, 2016)
Lake Towuti is a tectonic basin, surrounded by ultramafic rocks. Lateritic soils form through weathering and deliver abundant iron (oxy)hydroxides but very little sulfate to the lake and its sediment. To characterize the sediment biogeochemistry, we collected cores at three sites with increasing water depth and decreasing bottom water oxygen concentrations. Microbial cell densities were highest at the shallow site – a feature we attribute to the availability of labile organic matter and the higher abundance of electron acceptors due to oxic bottom water conditions. At the two other sites, OM degradation and reduction processes below the oxycline led to partial electron acceptor depletion. Genetic information preserved in the sediment as extracellular DNA provides information on aerobic and anaerobic heterotrophs related to Actinobacteria, Nitrospirae, Chloroflexi and Thermoplasmatales. These taxa apparently played a significant role in the degradation of sinking organic matter. However, extracellular DNA concentrations rapidly decrease with core depth. Despite very low sulfate concentrations, sulfate-reducing bacteria were present and viable in sediments at all three sites, as confirmed by measurement of potential sulfate reduction rates. Microbial community fingerprinting supported the presence of taxa related to Deltaproteobacteria and Firmicutes with demonstrated capacity for iron and sulfate reduction. Concomitantly, sequences of Ruminococcaceae, Clostridiales and Methanomicrobiales indicated potential for fermentative hydrogen and methane production. Such first insights into ferruginous sediments show that microbial populations perform successive metabolisms related to sulfur, iron and methane. In theory, iron reduction could reoxidize reduced sulfur compounds and desorb OM from iron minerals to allow remineralization to methane. Overall, we found that biogeochemical processes in the sediments can be linked to redox differences in the bottom waters of the three sites, like oxidant concentrations and the supply of labile OM. At the scale of the lacustrine record, our geomicrobiological study should provide a means to link the extant subsurface biosphere to past environments.